ANALISIS JARAK CELAH PENGUPAS DENGAN VARIASI PUTARAN POROS PENGUPAS PADA MESIN PENGUPAS KOPI BASAH (PULPER) - Hendrawan, Andre Budhi (Politeknik Harapan Bersama Tegal, 2021)
This study aims to determine the effect of setting the spacing of the slits and variations in the rotation of the shaft on the quality of the peeling on the coffee bean skin peeler machine and to determine the size of the spacing of the slits and the proper rotation of the shaft, to obtain a good quality of stripping on the coffee bean skin peeler machine. This study uses an experimental method, by comparing the distance of the peeler gap, there are 2 mm, 4 mm, and 6 mm at the shaft rotation speed of 365 rpm, 576 rpm, and 697 rpm on the peeling quality of the coffee bean skin peeler machine. The stripping quality at each peeler gap and shaft rotation speed will be analyzed and determined based on the quality category of the coffee beans that have been processed. The results showed that the percentage of stripping quality at a gap of 2 mm and a shaft rotation speed of 365 rpm reached 86%, a gap of 4 mm reached 70%, and at a gap of 6 mm it reached 55%. At a distance of 2 mm stripping gap and shaft rotation speed of 576 rpm it reaches 82%, 4 mm gap distance reaches 67%, and at 6 mm gap distance, it reaches 49%. At a distance of 2 mm stripping gap and 697 rpm shaft rotation speed reaches 80%, 4 mm gap distance reaches 59%, and at 6 mm gap distance reaches 40%. The exact distance of the stripper gap and the rotation of the shaft is obtained at the distance of the stripping gap of 2 mm and the shaft rotation speed of 365 rpm. At this distance, the percentage of good quality exfoliating coffee beans reached 86%, partially peeled 10%, and not peeled 4%.